Experimental Analysis on Utilization of Cigarette Butts in Fired Clay Bricks - Arvind Yadav; Vinay Kumar Singh Chandrakar (International Journal of Scientific Research in Civil Engineering, 2022)
The main objective of this study was to investigate the possibility of recycling CBs into fired clay bricks. The results of the investigation are very encouraging. The fired clay bricks produced by incorporating 0% to 10% CBs by mass, equivalent to approximately 0% to 30% by volume can be used in different applications according to the required strength. The major findings presented throughout this study are summarized as follows: The dry density of manufactured fired clay bricks decreased when CBs were incorporated into the raw materials. This is because the bricks became more porous as CB content increased. CB addition increased from 2.5% to 10% by mass. Low-density or light-weight bricks have great advantages in construction including lower structural dead load, easier handling, lower transport costs, lower thermal conductivity and a higher number of bricks produced per tones of raw materials. Light bricks can be substituted for standard bricks in different applications according to the required strength. CBs can also be regarded as a potential addition to the raw materials used in the manufacture of light-weight fired bricks. Therefore, manufactured clay- CB bricks are appropriate for these applications. The compressive strength of the bricks tested in this study was reduced markedly from 26 MPa (for 0% CBs) to 13, 5, 3 and 3 MPa for 2.5%, 5.0%, 7.5% and 10% of CB content respectively. Common minimum values recommended for characteristic compressive strength for non-load- bearing and load-bearing fired clay bricks are 3 to 5 MPa and 5 to 10 MPa